(untitled) (Journal of the College of Basic Education, 2022)
Teacher preparation is one of the most important pillars recognized globally, as it raises the scientific and professional level of the learner. Progress in knowledge makes the task of the teacher more important than it can be because he is the source of knowledge and he is the guide to the behavior of the learners. (Habib, 1989, p. 26). It is not possible to practice the teaching profession except with the presence of a well-prepared practical education program because it "is the essence of preparing the student-teacher professionally by developing his professional behavior and providing him with the initial experiences of the educational process and through developing his motor and professional skills, and providing him with the normal attitudes and behavioral patterns necessary to raise his teaching efficiency." (Abdul Khaleq, 1981, p. 113).